Measuring Students' Creativity in Arabic Speaking Class Based on Project Based Learning Model - Risna Rianti Sari; Alfiatus Syarofah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This study measures the development of creativity in a project carried out by students related to Arabic speaking skills. A qualitative method was adopted for the study involving 22 students divided into five FGD groups. The assessment of creativity through the FGD process until the project results is carried out by referring to the criteria and points contained in the rubric for assessing the creativity of the project that has been prepared beforehand. The results of this study describe the measurement of student project creativity based on the criteria of format, concept, creativity, spoken language used and the overall assessment of the project. From these measurements, it is known that students have average creativity in the design of Arabic speaking video projects. This means that a project can help foster a student's creative attitude, and help improve it, so it needs to be included in every lesson, especially learning languages such as Arabic.